A Study on Role of Antenatal Care in Pregnancy Outcome - K, Akhila; Kumar, Prasanth; Bhavani, Kenche (Journal of Maternal and Child Health, 2022)
Background: Antenatal care (ANC) and regular antenatal visits are one of the interventions that have the potential to improve both maternal and child survival. The utilization of antenatal services remains less than 60% in India. The study aimed to find out the association between ANC visits and pregnancy outcome. Subjects and Method: Cross-sectional study was conducted on 200 antenatal women in a tertiary care centre over a period of 3 months. After taking informed consent data was collected by interviewer technique using a pretested semi-structured questionnaire. Questionnaire includes information related to socio-demographic variables, number of ANC visits, delivery outcome (normal/ LSCS) low birth weight, stillbirths, and abortions. Thus, collected data was entered in excel and analyzed using epi info 7.22.6. The bivariate analysis was the chi-square test. Binary logistic regression was used to study the association between delivery outcome and its covariates. Logistic regression was also done to see the association between ANC visits and Low birth weight and stillbirths. Results: Out of 59 women who had less than 4 ANC visits had more number of abortions (18.6%) (OR= 32.08; CI 95%= 4.03 to 255.07; p<0.001), low birth weights (52.5%) (OR= 4.46; CI 95%= 2.31 to 8.62; p= 0.001), still births (8.5%) (OR= -1.00; CI 95%= -1 to -0.001 p=0.001), out of 22 illiterate mothers 16 of them had poor pregnancy outcomes (p= 0.002) and first ANC visit during first trimester had less complications (p <0.001). Binary logistic regression revealed significant association between delivery outcome and Socio-economic status (OR= 2.14; CI 95%= -1.47 to 3.13; p<0.001) as well as frequency of ANC visits (OR= 0.65; CI 95%= 0.55 to 0.77; p<0.001). Significant association was also observed between ANC visits and Low birth weight (OR= 0.52; CI 95%= -0.43 to 0.62; p <0.001). Logistic regression between ANC visits and stillbirths/abortion showed significant association (OR= 0.36 (CI 95%= -0.23 to 0.55; p<0.001). Conclusion: The study shows that less than 4 ANC visits, illiteracy increases the risk of poor pregnancy outcome. Women who had their first ANC visits during first trimester had less complications. Keywords: antenatal care, pregnancy outcomes, socio-demographic factors. Correspondence:Bhavani. Department of Community Medicine, Osmania Medical College, Hyderabad, Telangana. Email: bhavanikenche1969@gmail.com. Mobile: 9502710778.